A representation theorem for the linear quasi-differential equation (py′)′+qy=0 - J. G. O'Hara (International Journal of Mathematics and Mathematical Sciences)
We establish a representation for q in the second-order linear quasi-differential equation (py′)′+qy=0. We give a number of applications, including a simple proof of Sturm's comparison theorem.